DAMPAK E-MONEY DAN DIMENSI TRANSAKSI TERHADAP PERMINTAAN UANG DI INDONESIA - Nurhaida Purnamawati; Jihad Lukis Panjawa (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
Technological developments have shifted the payment system from paper based instruments to card based and electronic based instruments. The existence of innovation in finance will have an impact on the existence of money in society. Indonesia is the fourth most populous country and the need for money will also increase. The purpose of this study is to see how the impact of e-money and card dimensions on the demand for money in Indonesia. The data used in this study is monthly secondary data for 2017-2020. The method used in analyzing the data is the Engle Granger-Error Correction Model. The results of the study show that debit card transactions have a significant effect on the demand for money in Indonesia. Meanwhile, e-money and credit cards have no significant effect on the demand for money in Indonesia. This is because debit cards have been issued by many banks and are widely used by the people of Indonesia. However, if the use of e-money, debit cards and credit cards is used in the long term, it will have an impact on decreasing demand for money in Indonesia